The oldest representative of the bombyliid bee fly in the earliest Eocene French amber - Aude Maheu; Andre Nel (Acta Palaeontologica Polonica, 2020)
Eoconophorinadelfineae gen. et sp. nov., the oldest repre-sentative of the bee fly subfamily Bombyliinae, is described from the earliest Eocene Oise amber (France). It is charac-terized by the presence of mid tibial spurs, cylindrical ab-domen and a particular combination of wing venation char-acters. It is putatively attributed to the tribe Conophorini. This fossil is 53 Ma old, ca. 19 Ma older than the previ-ous oldest records of the subfamily, known as compression fossils. There are very few older bee flies, one from the Paleocene of Menat (France), and six from the mid-Creta-ceous Burmese amber, belonging to different subfamilies or of uncertain taxonomic position. Thus this fossil will be helpful for future calibration of phylogeny and dating of the bee flies.